Implementasi Projek Penguatan Profil Pelajar Pancasila Dimensi Beriman, Bertakwa kepada Tuhan Yang Maha Esa dan Berakhlak Mulia di SMP Negeri 11 Padang - Sumarni, Neti; Nurdin, Syafruddin; Kosim, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to describe and analyze The Project Strengthening The Profile of Pancasila Students in terms of faith, devotion to the Almighty God, and noble character at SMP Negeri 11 Padang. This research was conducted using a phenomenological approach, a qualitative type of research that looks closely and in detail at individual explanations and understandings of their experiences. Data collection was done using several techniques, namely; (a) Observation; (b) Interviews; and (c) Documentation of research results, which involved planning the formation of the facilitator team, then identifying the readiness of the educational unit, followed by the project implementation stage held in the hall with speakers such as Cerdik Pandai, and then a summative evaluation focusing more on the final results. The discussion begins with the planning of The Project To Strengthen The Profile of Pancasila Students, which involves forming the facilitator team and identifying the readiness of SMP Negeri 11 Padang. There are three things that need to be prepared to carry out this project, namely: 1) Readiness from the school side, including teachers and stakeholders, 2) Readiness from the school side, such as the hall, infocus, computer lab, health unit, 3) Readiness from external parties such as inviting speakers (Cerdik Pandai) as influential figures in the area. Then during the implementation, the students are gathered in the hall where the speakers explain and demonstrate how to cut shroud cloth and its parts. The summative evaluation then focuses on the results at the end of the activity, which is the year-end harvest festival. In conclusion, the planning involves forming the facilitator team, identifying school readiness, implementing the project in the hall, and then conducting a summative evaluation.